59.7k views
5 votes
Solve -2 | 3x - 6 | + 5 = 1

2 Answers

7 votes

Answer:

x = 1⅓, 2⅔

Explanation:

-2 | 3x - 6 | + 5 = 1

-2 | 3x - 6 | = 1 - 5

-2 | 3x - 6 | = -4

| 3x - 6 | = 2

3x - 6 = 2

3x = 8

x = 8/3 = 2⅔

3x - 6 = -2

3x = 4

x = 4/3 = 1⅓

User Mikestew
by
5.2k points
6 votes

Answer:

x =
(4)/(3), x =
(8)/(3)

Explanation:

Given

- 2 | 3x - 6 | + 5 = 1 ( subtract 5 from both sides )

- 2 | 3x - 6 | = - 4 ( divide both sides by - 2 )

| 3x - 6 | = 2

The absolute value function always returns a positive solution, however, the expression inside can be positive or negative, that is

3x - 6 = 2 ( add 6 to both sides )

3x = 8 ( divide both sides by 3 )

x =
(8)/(3)

OR

- (3x - 6) = 2, that is

- 3x + 6 = 2 ( subtract 6 from both sides )

- 3x = - 4 ( divide both sides by - 3 )

x =
(4)/(3)

As a check

Substitute these values into the left side of the equation and if equal to the right side then they are the solutions.

x =
(8)/(3) : - 2| 8 - 6 | + 5 = - 2| 2| + 5 = -2(2) + 5 = - 4 + 5 = 1 = right side

x =
(4)/(3) : - 2 | 4 - 6| + 5 = - 2| - 2| + 5 = - 2(2) + 5 = - 4 + 5 = 1 = right side

Thus the solutions are x =
(4)/(3) and x =
(8)/(3)

User Toothpick Anemone
by
5.4k points